2020
DOI: 10.3389/fonc.2020.01504
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlation of Wnt2 and COL8A1 With Colon Adenocarcinoma Prognosis

Abstract: Wnt2 mRNA is widely expressed in various tumor tissues. Wnt2 overexpression promotes tumor growth, migration, invasion, and metastasis. However, its underlying molecular action mechanisms and clinical implications in colon adenocarcinoma (COAD) remain unclear. mRNA expression data, obtained from tissue samples, and pathophysiological data of 368 COAD patients were obtained from the Cancer Genome Atlas (TCGA) database. Further, Pearson's correlation analysis was performed to explore the correlation between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Recent research has shown that COL8A1 is dysregulated in a variety of cancers. COL8A1 may affect the progression of colorectal cancer and the prognosis of patients by regulating focal adhesion-related pathways, and the expression of COL8A1 in colorectal cancer is related to the expression of Wnt2 and is linked to the poor survival of patients [ 28 , 29 ]. COL8A1 may promote breast cancer migration by affecting ECM receptor interactions and cooperation with other genes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that COL8A1 is dysregulated in a variety of cancers. COL8A1 may affect the progression of colorectal cancer and the prognosis of patients by regulating focal adhesion-related pathways, and the expression of COL8A1 in colorectal cancer is related to the expression of Wnt2 and is linked to the poor survival of patients [ 28 , 29 ]. COL8A1 may promote breast cancer migration by affecting ECM receptor interactions and cooperation with other genes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…COAD remains one of the most life-threatening malignancies in the world due to the complex molecular mechanisms. With the development of gene sequencing technology, some potential gene markers, including INHBA ( 24 ), COL8A1 ( 25 ), and GABRD ( 26 ), correlated with poor prognosis for COAD patients have been identified. Nevertheless, the number of such biomarkers in COAD tumorigenesis is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the four identified markers in the model, elevated expression of COL8A1 has been found in CAFs and was significantly associated with a high risk of death in head and neck squamous cell carcinoma (Lai et al, 2019). Zhang et al identified COL8A1 as the prognostic hub gene highly correlated with Wnt2, which is elevated selectively in CAFs, and high coexpression of COL8A1 and Wnt2 was an independent adverse prognostic factor for colon cancer patients (Katoh, 2001;Zhang et al, 2020) proliferation and promoted the apoptosis of GC cells (Zhou et al, 2020). As for SPOCK1, studies have proved SPOCK1 as an EMT-related marker that was closely correlated with tumorigenesis and invasiveness in gastric cancer (Yan et al, 2017;Chen et al, 2018), prostate cancer (Wang et al, 2016), pancreatic cancer (Li et al, 2020), gallbladder cancer (Shu et al, 2015), and lung cancer (Miao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%